2022
DOI: 10.3389/fendo.2022.906586
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of the Atypical Chemokine Receptor 3 (ACKR3) in Cardiovascular Diseases

Abstract: Chemokines, and their receptors play a crucial role in the pathophysiology of cardiovascular diseases (CVD). Chemokines classically mediate their effects by binding to G-protein-coupled receptors. The discovery that chemokines can also bind to atypical chemokine receptors (ACKRs) and initiate alternative signaling pathways has changed the paradigm regarding chemokine-related functions. Among these ACKRs, several studies have highlighted the exclusive role of ACKR3, previously known as C-X-C chemokine receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 104 publications
1
13
0
Order By: Relevance
“…Genetic loss of RAMP3 eliminated the cardioprotective effects of GPR30 activation in chronic hypertension and cardiac hypertrophy mouse model ( Lenhart et al, 2013 ) . Studies in mice have also pointed to a potential role of ACKR3 and its regulation by RAMP3 in cardiovascular disease ( Duval et al, 2022 ). Mackie et al showed that ACKR3 and RAMP3 form a complex that can scavenge AM, which in turn reduces AM bioavailability and decreases signaling through the CALCRL-RAMP3 complex, a pathway thought to be involved in angiogenesis ( Mackie et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic loss of RAMP3 eliminated the cardioprotective effects of GPR30 activation in chronic hypertension and cardiac hypertrophy mouse model ( Lenhart et al, 2013 ) . Studies in mice have also pointed to a potential role of ACKR3 and its regulation by RAMP3 in cardiovascular disease ( Duval et al, 2022 ). Mackie et al showed that ACKR3 and RAMP3 form a complex that can scavenge AM, which in turn reduces AM bioavailability and decreases signaling through the CALCRL-RAMP3 complex, a pathway thought to be involved in angiogenesis ( Mackie et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…ROBO2 [760], VCAM1 [761], GRP (gastrin releasing peptide) [762], FABP4 [763], ANO1 [764], SOX6 [765], TFAP2C [766], RAMP3 [767], PLA2G7 [768], MMP12 [769], FAIM2 [770], APOD (apolipoprotein D) [771], LAG3 [772], SOX18 [773], F2RL2 [774], CCR1 [775], FLT1 [776], FABP5 [629], TRPC3 [777]. THSD7A [778], DKK2 [779], PRKCB (protein kinase C beta) [780], DHCR24 [781], PDE3B [782], BMP4 [783], IL1RL1 [784], MYPN (myopalladin) [785], PLCG2 [786], PRL (prolactin) [787], WNT5A [788], MEOX1 [789], TIMP3 [790], FRZB (frizzled related protein) [791], CPE (carboxypeptidase E) [792], ADAMTS9 [793], NDNF (neuron derived neurotrophic factor) [794], PDGFB (platelet derived growth factor subunit B) [795], PIK3CG [796], LDLR (low density lipoprotein receptor) [797], CD4 [798], TRPA1 [799], F2RL3 [800], C1QL1 [801], ADAMTS5 [802], PDE4B [803], NES (nestin) [804], TH (tyrosine hydroxylase) [805], MMP8 [806], KDR (kinase insert domain receptor) [807], ADRB2 [808], ACKR3 [809], PTPRC (protein tyrosine phosphatase receptor type C) [810], KL (klotho) [811], KL (klotho) [812], PLAU (plasminogen activator, urokinase) [813], CCND2 [814], PTGS1 [815], INSIG1 [816], IRX2 [817], SIGLEC1 [818], UCN2 [819], CYP2J2 [820], CYP1A1 [821], ASTN2 [822], NTN1 [823], PDGFD (platelet derived growth factor D) [824], MSTN (myostatin) [663], LEPR (leptin receptor) [664], IL15 [825], CACNA1H [826], BMP2 [827], SYT7 [<...…”
Section: Discussionmentioning
confidence: 99%
“…Still, several DEGs short-listed in our study (Supplementary Tables S3 , S4 ) have been previously linked to hypoxia. Among the genes upregulated in hypoxia in both DMSO- and onametostat-treated cells, the atypical chemokine receptor 3 ( ACKR3 ) has been explored in the context of cardiovascular diseases and inflammation 57 , the nerve growth factor ( NGF ) in the context of angiogenesis in non-small cell lung cancer 58 , and the 4-hydroxyphenylpyruvate dioxygenase ( HPD ) in the context of metabolic reprogramming in lung cancer 59 . In case of the hypoxia-upregulated DEGs found only in the DMSO-treated cells, the heme oxygenase-1 ( HMOX1 ) and isthmin1 ( ISM1 ) have been reported as the direct downstream targets of the hypoxia-inducible transcription factor (HIF) 60 , 61 , whereas indirect regulation mechanism by HIF has been proposed for the C-X-C motif chemokine ligand 3 ( CXCL3 ) 62 .…”
Section: Discussionmentioning
confidence: 99%